Numerical analysis of lateral torsional buckling of steel i-beams with and without web-openings under fire - Benyettou, S. (2020)
During the last decade, there has been great concern about fire applied loading effect on structural steel frames and their elements, especially when instability phenomenon arises due to high temperatures [1].The objective of this paper is to study the fire behaviour of I-beam steel simply supported members with and without web openings under lateral torsional buckling accounting geometric imperfection and residual stress.